2016
DOI: 10.17577/ijertv5is110075
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Automobile Radiator using MWCNT-Water Nanofluid

Abstract: The heat generated in an automobile engine needs to be extracted and dissipated for its efficient working. The objective of this experiment was to improve the thermohydraulic performance of the radiator which can be achieved by using nanofluids as engine coolant for increasing the heat rejection capacity on the coolant side. The present study investigates the performance of MWCNT-water nanofluid at different temperatures (50, 60, and 70 o C). The results indicate that maximum increase in thermal capacity was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Wilson CA studied the stability studies on nano fluids with diamond nano particles with respect to time as shown in fig 2 [13]. Paresh Machhar, Falgun Adroja, synthesized a nano fluid by dispersing TiO 2 in water and observed it was stable for several days without sedimentation as shown in fig3 [14]. Lee et al studied the aqueous Al 2 o 3 nano fluid and found that thermal conductivity increased when compared with the use of water as coolant [15].…”
mentioning
confidence: 99%
“…Wilson CA studied the stability studies on nano fluids with diamond nano particles with respect to time as shown in fig 2 [13]. Paresh Machhar, Falgun Adroja, synthesized a nano fluid by dispersing TiO 2 in water and observed it was stable for several days without sedimentation as shown in fig3 [14]. Lee et al studied the aqueous Al 2 o 3 nano fluid and found that thermal conductivity increased when compared with the use of water as coolant [15].…”
mentioning
confidence: 99%